Population Dynamics of Clostera fulgurita and its Principal Natural Enemies in Punjab - Sangha, K.S.; Sohi, A.S. (Indian Journal of Agroforestry, 2020)
Seasonal abundance of Clostera fulgurita (Walker) and its principal natural enemies, host range, nature and extent of damage caused by this defoliator were studied in poplar block plantations during 2002-2003. Clostera fulgurita fed on poplar and willow only. Two peaks of population were recorded based on per cent damaged leaves, larvae and pupae per meter branch length during the year. Neonate larvae fed on chlorophyll and skeletonised the leaves. The fifth instar larvae caused 70% of the total damage caused by all the instars. A predatory bug, Canthecona furcellata and a larval parasitoid, Aleoides percurrens were recorded as biocontrol agents contributing towards the regulation of population of Clostera fulgurita in the fields.